Evaluation of Glutathione Peroxidase and Glutathione Reductase Enzymes in Iraqi Patients with Colorectal Cancer - E. Mahrose, Noor; A. Hassan, Firas; Jebali, Jamel; Mohammed, Salam (Al-Nahrain Journal of Science, 2024)
Glutathione peroxidase, and glutathione reductase Enzymes have a significant role in colorectal cancer (CRC) progression. The objective of this article is to measure glutathione peroxidase, and glutathione reductase enzymes in colorectal cancer patients and compare them with healthy subjects. Seventy newly diagnosed colorectal cancer patients were enrolled in the present study and divided as follows; Group A: (n=32) with an age range (of 20-40 years); Group B: (n=38) with age range (41-60 years). For comparison, total of (30) healthy subjects were also inserted in the current study divided into patients in the same manner.  Serum levels of glutathione peroxidase and glutathione reductase enzymes were measured for patients and controlled by the ELISA technique. The current study shows that serum glutathione peroxidase levels varied significantly in (the 20-40 years) group when comparing the patient and control group (395.5 ng/ml vs. 71.61 ng/ml, p-value less than 0.0001) and also in (41-60 years) group with mean (469.4 ng/ml vs. 106.3 ng/ml, p-value less than 0.0001) for patients and control groups respectively. Antioxidant enzymes including glutathione peroxidase, and glutathione reductase were increased in colorectal cancer patients compared to healthy subjects, significantly. According to the current study, the evolution of these enzymes can be used to understand the pathophysiology of disease and also to diagnose the colorectal cancer